Alternative Control Methodology of Grid-Supporting Grid-Forming Power Converter with a Proportional Complex-Vector Controller - Somkiart Khongkhachat; Surin Khomfoi (My University, 2023)
An alternative control methodology for a grid-supporting grid-forming (GSGFm) power converter operating within a synchronous rotating reference frame (SRRF) is developed in this research. The proposed methodology combines a proportional (P)-based controller with a complex-vector (CV) controller to effectively mitigate distortions. The cascade voltage and current control structure employed in this methodology leverages a two-proportional controller to precisely regulate the dq-components of voltage and currents. Additionally, a two-complex-vector controller is utilized to attenuate periodic disturbances that may arise during operation. Experimental results have been conducted to evaluate and validate the performance of the suggested methodology. The obtained results provide empirical evidence supporting the effectiveness and robustness of the proposed control approach.
Keywords: Microgrid Control and Optimization; Multilevel Inverters and Converters; Islanding Detection in Power Systems